Practical bandaging, including adhesive and plaster-of-Paris dressings / by Eldridge L. Eliason ; 171 original drawings and photographs. - Eliason, Eldridge L., 1879-1950. (Tufts University. Tisch Library., 2020)
Third edition revised.; xiv, 128 pages : illustrations ; 21 cm.; Includes index.; Tisch In-House Digitization 2020-01-28